1998
DOI: 10.1007/s002040050494
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of fumonisin B 1 : implication of lipid peroxidation and inhibition of protein and DNA syntheses

Abstract: The effects of fumonisin B1 (FB1) from Fusarium moniliforme on lipid peroxidation and protein and DNA syntheses were studied in monkey kidney cells (Vero cells). FB1 was found to be a potent inducer of malondialdehyde (MDA), one of the secondary products formed during lipid peroxidation. At 0.14 microM (0.1 microg/ml), FB1 induced 0.496 +/- 0.1 nmoles of MDA/ mg protein, compared to the control level 0.134 +/- 0.01 nmoles of MDA/mg protein (P < 0.005). No inhibition of protein or DNA synthesis was observed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 31 publications
4
45
2
Order By: Relevance
“…FB 1 has been reported to be a nephrotoxic for kidney (Bucci et al, 1998;Voss et al, 2001;Howard et al, 2001) and to provoke in vitro and in vivo degenerative and/or apoptotic damages in tubular epithelium of kidneys in rats or pigs (Dragan et al, 2001, Stoev et al, 2012, which was confirmed by the present study. FB 1 is also reported to impair protein synthesis in cells, which could lead to further degenerative changes in kidneys or liver, the target organs responsible for elimination or detoxification of mycotoxins (Abado-Becognee et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…FB 1 has been reported to be a nephrotoxic for kidney (Bucci et al, 1998;Voss et al, 2001;Howard et al, 2001) and to provoke in vitro and in vivo degenerative and/or apoptotic damages in tubular epithelium of kidneys in rats or pigs (Dragan et al, 2001, Stoev et al, 2012, which was confirmed by the present study. FB 1 is also reported to impair protein synthesis in cells, which could lead to further degenerative changes in kidneys or liver, the target organs responsible for elimination or detoxification of mycotoxins (Abado-Becognee et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in lipid peroxidation leads to cell damage. According to Karine et al [1], once lipid peroxidation is initiated, it can easily be propagated in the cellular environment where unsaturated lipids and oxygen are present. The oxidation of lipids is propagated by radical mediated chain reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Two further theories have been proposed to explain the mechanism of action of FB 1 : disruption of fatty acid metabolism and the induction of oxidative stress, and modulation of gene expression (Abado-Becongnee et al, 1998;Mobio et al, 2000). In contrast to the sphingolipid imbalance theory, which can account for all of the known effects of FB 1 either in vivo or in vitro, these alternative theories cannot.…”
Section: Mechanism Of Actionmentioning
confidence: 99%